Facilitators of and barriers to buprenorphine initiation in the emergency department: a scoping review - Nikki Bozinoff; Erin Grennell; Charlene Soobiah; Zahraa Farhan; Terri Rodak; Christine Bucago; Katie Kingston; Michelle Klaiman; Brittany Poynter; Dominick Shelton; Elizabeth Schoenfeld; Csilla Kalocsai (Elsevier, 2024)
Summary: Buprenorphine initiation in the Emergency Department (ED) has been hailed as an evidence-based strategy to mitigate the opioid overdose crisis, but its implementation has been limited. This scoping review synthesizes barriers and facilitators to buprenorphine initiation in the ED, and uses the Consolidated Framework for Implementation Research and a critical lens to analyze the literature. Results demonstrate an immense effort across the U.S. and Canada to implement ED-initiated buprenorphine. Facilitators include multidisciplinary addiction teams and co-located, low-barrier, harm reduction-informed services to support transitions. Barriers include a failure to address structural stigma, client complexity, and an increasingly toxic drug supply. The literature also misses the opportunity to include the perspectives of service users, health administrators, and learners. Increased coordination of implementation efforts, and a shift to equitable and inclusive opioid agonist therapy initiation pathways are needed across the U.S. and Canada.